GROWTH RATE OF THE {0001} AND {0111} FACES OF QUARTZ AS A FUNCTION OF TEMPERATURE - Ostapenko G.T.; Mitsyuk B.M. (My University, 2006)
The growth and dissolution rates of quartz in water and various aqueous solutions have long been studied by many researchers. A polar diagram was constructed for the growth rate of main quartz faces and other artificial surfaces. However, an important kinetic parameter, the activation energy of the growth of various quartz faces, requires further refinement.